The Roman Republic to 49 BCE - Yarrow, Liv Mariah. (Cambridge)
xxxvii, 273 sayfa
Keywords: “The narrative of Roman history has been largely shaped by the surviving literary sources, augmented in places by material culture. The numerous surviving coins can, however, provide new information on the distant past. This accessible but authoritative guide introduces the student of ancient history to the various ways in which they can help us understand the history of the Roman republic, with fresh insights on early Roman-Italian relations, Roman imperialism, urban politics, constitutional history, the rise of powerful generals and much more. The text is accompanied by over 200 illustrations of coins, with detailed captions, as well as maps and diagrams so that it also functions as a sourcebook of the key coins every student of the period should know. Throughout, it demystifies the more technical aspects of the field of numismatics and ends with a how-to guide for further research for non-specialists“ --